2016
DOI: 10.1016/j.cgh.2016.05.017
|View full text |Cite|
|
Sign up to set email alerts
|

Consequences of Increasing Time to Colonoscopy Examination After Positive Result From Fecal Colorectal Cancer Screening Test

Abstract: BACKGROUND & AIMS Delays in diagnostic testing after a positive result from a screening test can undermine the benefits of colorectal cancer (CRC) screening, but there are few empirical data on the effects of such delays. We used microsimulation modeling to estimate the consequences of time to colonoscopy following a positive result from a fecal immunochemical test (FIT). METHODS We used an established microsimulation model to simulate an average-risk United States population cohort that underwent annual FIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 57 publications
4
95
1
Order By: Relevance
“…The only published source that we found reporting delayed diagnosis was the Meester et al study. 139 This study used a microsimulation model to calculate the effect of delay to colonoscopy on an average-risk population cohort in the USA who underwent annual FIT screening (from the age of 50 to 75 years), with follow-up colonoscopy examinations for individuals with positive results in the following 12 months. For the scenario of diagnostic follow-up at 12 months from a positive FIT, diagnosed cancers shifted towards more advanced stages, but still with only 8% in stage D. Regardless of the precise delay and its effect on progression, the cost-effectiveness results did not change significantly assuming 6 months' or 1 year's delay and so we decided not to run an additional scenario for a smaller delay.…”
Section: Doi: 103310/hta21330mentioning
confidence: 99%
“…The only published source that we found reporting delayed diagnosis was the Meester et al study. 139 This study used a microsimulation model to calculate the effect of delay to colonoscopy on an average-risk population cohort in the USA who underwent annual FIT screening (from the age of 50 to 75 years), with follow-up colonoscopy examinations for individuals with positive results in the following 12 months. For the scenario of diagnostic follow-up at 12 months from a positive FIT, diagnosed cancers shifted towards more advanced stages, but still with only 8% in stage D. Regardless of the precise delay and its effect on progression, the cost-effectiveness results did not change significantly assuming 6 months' or 1 year's delay and so we decided not to run an additional scenario for a smaller delay.…”
Section: Doi: 103310/hta21330mentioning
confidence: 99%
“…However, the effectiveness of fecal screening tests depends on timely follow-up diagnostic colonoscopy of patients with positive test results; guidelines generally recommend colonoscopy within 1 to 3 months (5, 7, 8). A long interval between a positive test result and colonoscopy can have important implications for CRC prognosis (911). …”
mentioning
confidence: 99%
“…Prior work has shown that complete diagnostic colonoscopy follow-up rates after abnormal guaiac FOBT and FIT may be as low as 22% (9)(10)(11)(12). Further, a recent modeling study has suggested that delay in follow-up results in higher CRC stage at presentation, incidence, and mortality; the relative reduction in life-years gained associated with screening was estimated to be 10% lower for diagnostic colonoscopy within two weeks vs 12 months after a positive FIT (13).…”
mentioning
confidence: 99%